Factor Analysis of Minimum Wage and Labor Force Participation Rate on Unemployment Rate in Indonesia - Erna Apriani; Dian Rachmawati Afandi; Indra Permana; Fachrial Banyu Asmoro; Akfika Rizky Sabilla (Universitas Syiah Kuala, 2025)
The increasingly massive unemployment rate is a very bad condition for the domestic economy; the role of the government is very important in minimizing unemployment. This condition is a very heavy burden for the community and the government; if it continues, it will continue to impact the decline in people's purchasing power. From this background, the purpose of this research is to analyze directly the minimum wage variable and the level of labor force participation in the unemployment rate, as well as the direct effect of the minimum wage on labor force participation, then the indirect effect of the minimum wage on the unemployment rate through the mediation of the level of labor force participation. The data analysis method used in the research is path analysis on the minimum wage variable, unemployment rate, and labor force participation rate as intervening variables. The results showed that the direct relationship between minimum wage and labor force participation rate had no effect. The direct relationship between minimum wage and unemployment rate had no effect. The direct relationship between the labor force participation rate and the unemployment rate had a positive effect. The indirect relationship between minimum wage and unemployment rate by the mediation dimension of labor force participation rate did not mediate the two.